"Roger Broke His Tooth. However, He Went to the Dentist": Why Some Readers Struggle to Evaluate Wrong (and Right) Uses of Connectives. Issue 2 (7th February 2020) - Zufferey, Sandrine; Gygax, Pascal
ABSTRACT: Understanding discourse connectives is an important step to achieving effective verbal communication. Yet, the ability of adult native speakers to understand the broad range of connectives found in most Indo-European languages has seldom been assessed. In this article we demonstrate that some adults have difficulties recognizing correct and incorrect uses of connectives in their native language. In Experiment 1 we show that adults have a lower ability to understand less frequently used connectives from the written mode than more frequently used ones. We also report that such an ability depends on participants' exposure to print (as measured by the Author Recognition Test), in turn correlating with higher general grammatical competence. In Experiment 2 we find that the performance of an adult increases with connectives that are used in both speech and writing, although differences are still present between connectives and between participants differently exposed to print. We conclude that connectives represent an area of complexity for some adults with less exposure to print and poorer grammatical competences.